EXPLORATORY STUDY OF EMPLOYEE ENGAGEMENT - Tita Miawati; Widodo Sunaryo; Nancy Yusnita (UNIVERSITAS PAKUAN, 2020)
Employee engagement is now recognized as an important topic in the company because it relates with turnover rate, productivity of employee and finally to the company growth. A study conducted to describe the finding of an effort to increase the effectiveness of engagement implementation by company in order to increase level of employee engagement. The study used qualitative research method through exploratory study in a multinational company in Jakarta. Data obtained through interviews with key leaders of the company to find out how the implementation of engagement conducted by the company, and a Focus Group Discussion of employee groups to determine the condition of employee engagement. The researchers analyzed the data from both of company and employees to see if there is a gap between engagement implementation by the company and the conditions of employee engagement. To obtain the validity of the data, researchers used triangulation techniques carried out by experts in the HR field. The study found that the company's efforts to implement employee engagement had not been carried out optimally and equally on all engagement indicators. Likewise, the condition of employee engagement has not yet reached optimal conditions. The conclusion described that there is a gap between company’s engagement implementation program and the engagement conditions felt by employees. Thus, it is necessary to make efforts to improve the effectiveness of engagement implementation so that increasing the employee engagement bring contributes to the company's growth